Competitiveness of the High Technology Sector and Sustainable Development Economic - Selected Issues - Małgorzata JUCHNIEWICZ; Magdalena ŁADA (Communications of International Proceedings, 2021)
An important role in shaping a competitive economy is assigned to the high-tech sector. It houses technologically advanced industrial enterprises and knowledge-intensive technologically advanced services. Technologically advanced enterprises, despite the short life of the sector and its specificity, quickly adapt to new conditions and requirements set by society and play an increasingly important role in national economies. It was a premise for a synthetic discussion of the theoretical dependencies between the competitiveness of the advanced technology sector and sustainable economic development, as well as an indication of an empirical research gap in this area.
Keywords: Competitiveness; Sustainable Economic Development; High Technology Sector